Austerity in reverse: Korea, capabilities, and crisis. Issue 1 (2nd January 2020) - Potter, Cuz; Kim, Jeeyeop
ABSTRACT: Development is austerity in reverse. And austerity is development in reverse, a form of de-development. This paper argues that austerity is a neoliberal technology for returning countries to positive economic growth that reduces social spending and thereby reverses development. Drawing on Sen and Nussbaum's human capabilities approach, an exploration of Korea's development since 1960 supports this and three additional claims. First, the expansion of capabilities in Korea is tied to democratization and exponential increases in social spending. Second, Korea's experience with financial crises and austerity programmes demonstrate that increased social spending is compatible with rapid recovery. Third, Korea's roll out of neoliberal technologies and economic transformation since the 1980s have undermined the capabilities developed during earlier industrialization. Fourth, the importance of housing as a vital tool for political legitimation, especially since democratization, has sustained political interest in providing better housing, suggesting that social movements are essential to protecting social spending.